PERANCANGAN DAN PEMBUATAN MESIN LAS ELEKTRODA GANDA UNTUK MENINGKATKAN KUALITAS HASIL LAS - Yustiasih Purwaningrum; Medilla Kusriyanto; Rudi Kurniawan (Faculty of Industrial Technology Universitas Islam Indonesia, 2018)
Double Metal Arc Welding Gas Electrodes (DE-GMAW) is a new welding process that separates the melting current into a base metal current and a controlled current by adding a TIG torch to a conventional GMAW system to form an alternative path that will flow through the current. This makes it possible to reduce the current passing through the base metal, so that the heat input in the base metal can be controlled at the desired level. Research has been done to know the parameters for the welding process run stable between welding wire and torch TIG as current cutter. Parameters that affect the stability of the control system are Bypass Electrodes, Tungsten Distance to Welding Electrodes, Tungsten Distance to Workpieces, Torch GMAW Tube Distance to Workpieces, Angles between Tungsten and Welding Wires. To control the base metal current at the desired level, a group of power resistors is added in the control system. In this study, the welding is done using 18 V voltage by using several variations of the number of resistors. From the research shows that the control system developed can adjust the current cut in a large range to maintain the base metal current at the desired level. The welding results using the DE-GMAW control system show the physical properties of the weld result better when compared with welding without using current control system.